THE MOTHERHOOD INSTINCTS OF MALEFICENT AGAINST HER EX-BOYFRIEND’S CHILD IN THE MOVIE “MALEFICENT 1 & 2” - Audina, Chivani Nadia; Mahmud, Murni (Journal of English Literature and Linguistic Studies, 2025)
This research discusses Maleficent's motherhood instinct towards her former lover's child in the movie "Maleficent 1 & 2". This research aims to analyze and understand the role and changes in Maleficent's character as a surrogate mother figure towards the child. The qualitative method of analysis involves an in-depth review of the two films, focusing on Maleficent's interactions with the child, the dynamics of their relationship, and the impact of key events in the narrative on Maleficent's character evolution. The findings of this study highlight Maleficent's emotional complexity and inner conflict in assuming the role of surrogate mother. The results of the analysis show that Maleficent's character undergoes a profound emotional transformation, from a conflicted beginning to finally becoming a figure who has a strong emotional bond with the child. Factors such as betrayal, forgiveness, and character growth are the main focus in discussing the dynamics of this relationship. In addition, this study can provide additional insights into the representation of gender roles and family relationship dynamics in the context of fantasy films. As such, this research contributes to our understanding of character complexity in film narratives, especially in portraying the unexpected maternal instincts of characters commonly associated with evil or antagonistic sides.Keywords: Instinct, Conflict, Motherhood, Character